Codeposition of Particles: Role of Adsorption of the Electroactive Species. - Bengoa, L. N. (2016)
Cu-Al2O3 composite coatings were obtained from a 0.2MCu2+ and 0.6Mmonosodium glutamate electrolytewhose pHwas adjusted at different values in the 3–10 range. Particle charging behavior was studied through ζ-potential measurements and the potential of zero charge of the electrode was determined using Electrochemical Impedance Spectroscopy. Scanning Electron Microscopy was used to characterize coatings surface and to detect particle incorporation. The wt% of alumina in the deposits was estimated using Energy Dispersive Spectroscopy performed on their cross section. Under these experimental conditions high incorporation of particles into the copper matrix was observed, which was ascribed to the increased Cu2+ adsorption on Al2O3 surface induced by the presence of glutamate in the electrolyte. It was found that hydration forces strongly influence the codeposition of particles as proposed by Fransaer et al. The results were used to identify the relevant steps in the process and to develop a semi-empirical model.